How Knowledge Influences Antibiotic Adherence Among Outpatients: A Cross-Sectional Study at Indonesian Primary Health Centers - Fidyawati; Oqui, Maximiano; Pinto, Joaquim (International Journal of Health Concord, 2025)
Background: Antibiotic resistance poses a significant global health challenge, often exacerbated by inappropriate antibiotic use and poor patient adherence to prescribed regimens. Understanding the factors influencing antibiotic knowledge and adherence among outpatients is critical to improving treatment outcomes and mitigating resistance development. This study aimed to analyze the relationship between patients’ knowledge and their adherence to antibiotic use at Puskesmas Gadung Kab. Buol Methods: A cross-sectional descriptive study was conducted involving 42 outpatient respondents between January and February 2024. Data on sociodemographic characteristics, knowledge of antibiotics, and adherence behavior were collected using structured questionnaires. Descriptive statistics and Spearman’s rho correlation test were applied to analyze the data Result: The findings revealed that a substantial proportion of respondents demonstrated moderate to good knowledge about antibiotics, with a notable association between higher knowledge levels and better adherence to antibiotic regimens. The majority of participants complied with prescribed antibiotic use, particularly those with sufficient understanding of antibiotic resistance and appropriate usage. The study also identified that demographic factors such as age, gender, education, and occupation influenced both knowledge and adherence behaviors. The statistical analysis confirmed a significant positive correlation between knowledge and adherence, underscoring the importance of patient education Conclusion: In conclusion, enhancing patients’ knowledge about antibiotics is essential to improving adherence and combating antibiotic resistance. Healthcare providers should prioritize continuous educational interventions and counseling to reinforce correct antibiotic use among outpatients. Future research with larger samples and diverse settings is recommended to generalize the findings and explore additional factors influencing adherence.